PREVALENCE OF OVERWEIGHT AND OBESITY AND ASSESSMENT OF LIPID PROFILE AND FASTING BLOOD GLUCOSE LEVELS AMONG FEMALE PREMEDICAL STUDENTS AT NNAMDI AZIKIWE UNIVERSITY, NNEWI CAMPUS, NIGERIA - Onwubuya, Emmanuel Ikechukwu; Ukibe, Nkiruka Rose; Kalu, Ofia Anya; Emelumadu, Obiageli Fidelia; Monago, Ifeoma Nwamaka; Ukibe, Solomon Nwabueze (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Obesity is a major public health issue and a significant risk factor for metabolic disorders. This prospective study was aimed at evaluating the prevalence of obesity, lipid profiles, and fasting blood glucose (FBG) among female premedical students of NAU, Nnewi Campus, Nigeria. Methods: A total of 320 female premedical students aged 18–35 years were recruited. The participants were classified using Body mass index(BMI) as underweight (35), overweight (104), obese (26), and control (155). FBG and lipids were estimated using enzymatic methods. Obesity was assessed using BMI and waist circumference. Blood pressure (BP) was measured using accoson sphygmomanometer. Results: The study observed 10.9% underweight, 32.5% overweight, and 8.1% obesity. Underweight was higher among participants aged 18–23 years (48.6%), while overweight and obesity were more among participants aged 24–29 years (57.7% and 53.8%). Central obesity was observed in 28.8% of participants. BPs were higher in obese and overweight participants than in other groups. FBG was higher in obese and overweight participants than in other groups. The mean total cholesterol (TC) and low-density lipoprotein cholesterol (LDLC) were significantly higher in obese and overweight participants, while high-density lipoprotein cholesterol (HDLC) was significantly lower when compared to their corresponding values in underweight and control participants (p<0.05). Conclusions: The study showed high prevalence of underweight, overweight, and obesity among the study population. The significantly higher levels of TC, LDLC, FBG, and elevated BP with significantly lower HDLC in overweight and obese participants compared to control suggests a possible risk of dyslipidemia, diabetes mellitus, and hypertension. The significant correlation between the lipid parameters, FBG, and anthropometric indices suggests high-risk cardiovascular disorders.